QSAR Studies of Anti-malarial Agents: 2,4-DiaminoPyrimidine Derivatives - Neekhara, Richa; J. Mishra, Brijeshkunvar; Hari Narayana Moorthy, N.S. (Asian Journal of Chemistry, 2010)
The discovery and development of a novel target site to treat malaria is still continued worldwide. The bifunctional enzyme dihydrofolate reductase-thymidylate synthetase (DHFRTS) is found in malarial parasite. The DHFR domain of the enzyme plays an important role in nucleic acid synthesis, which acts as an attractive target for designing antimalarial compounds. The 2,4-diaminopyrimidine derivatives have been reported to be antimalarial agents by virtue of their inhibition of DHFR. The physico-chemical descriptors, indicator variables and biological activity (TM4, K1CB1) of 2,4-diaminopyrimidine derivatives were considered for quantitative structure activity analysis. Highly correlated significant equations were obtained from the multiple regression analysis and are taken for further analysis as represented below. TM4 : –log IC50 = 0.523751(±0.493089)π – 0.0391451(±0.0372016)MR – 1.64545(±1.32314) IRI + 1.20497(±0.887005)IR5 – 0.735828(±0.755899) n = 28, r = 0.668, r2 = 0.447, Ftest = 4.6562, s = 0.642, Q2 = 0.314 K1CB1: –log IC50 = – 0.677(±0.613)σm – 0.595(±0.434)σp + 0.478(±0.317) IR2 + 0.628(±0.791) IRI – 1.058 (±0.247) n = 26, r = 0.763, r2 = 0.583, Ftest = 7.355, s = 0.362 The results show that for activity against wild type (TM4) pf DHFR, hydrophobicity of the substituents (π) and substituent at position R5 was important (positive correlation) whereas substituent at R1 position and a higher electron polarizability, the value of the substituent (MR) would be detrimental to the activity (negative correlation). On the other hand, the activity against S108N mutant form (K1CB1) of pf DHFR, substituents at R1 and R2 would be beneficial whereas the electronic property of the molecule was found to be detrimental to the activity.